Konsep Pendidikan Andragogi dalam Perspektif Pendidikan Islam - Khairrurraziqin, Khairrurraziqin; Sari, Dewi Purnama; Fadilah, Fadilah Purnama (JOEAI (Journal of Education and Instruction), 2020)
This research aims to obtain information on the concept of Andragogi education in the perspective of Islamic Education. This research is a qualitative study of literature using content analysis. The results of the study are informed if the concept of Andragogi Education is the art and science of teaching adults to learn, how to help adults learn according to their needs and efforts to motivate adults to learn using their experiences to achieve new learning experiences. There are 4 basic assumptions in andragogi education that include concepts about learners, the function of experience, learning readiness and learning attestation. In conclusion, in the Perspective of Islamic Education, the concept of Andragogi education is a method of learning that is relevant to the atmosphere of adult learning found in the Qur'an and hadith, namely the method of awareness, method of practice and method of learning in the Hadith of the Prophet SAW. Keywords: Andragogi, The Concept of Education, Islamic Education, Perspectives